Uji Terbatas Keefektifan Pembelajaran Menulis Teks Deskriptif Berbasis M-Learning - Hany Uswatun Nisa; Agnes Apryliana (Jurnal Kajian Bahasa, Sastra dan Pengajaran (KIBASP), 2020)
The purpose of this study, namely to test the effectiveness of the m-learning instructional media conducted on students of SMP N 1 Banjarharjo Brebes. Type of research, namely quasi experimental research using grade 7. The study uses an assessment instrument of the written description. The results of the study show the score t count 7,330 and t table price 2,042 for 5%. Learning by applying m-learning has prove to be effective. There is an increase in the results of writing descriptive text for students of SMP N 1 Banjarharjo Brebes in learning to write description text. Keywords: m-Learning, Write, Description